2002
DOI: 10.1210/jcem.87.4.8406
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle Effects on the Neurohumoral and Autonomic Nervous Systems Regulating the Cardiovascular System

Abstract: Gonadal hormones may affect homeostatic mechanisms regulating the cardiovascular system. We investigated this relationship at five different crucial hormonal time points along the menstrual cycle. Eight eumenorrheic healthy subjects underwent a battery of autonomic tests, hemodynamics, and volume-regulatory hormone measurements. Fluid-regulatory hormones, plasma renin activity, and aldosterone increased along the luteal phase (P = 0.003 and 0.02, respectively), whereas rest supine-corrected hematocrit declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 33 publications
6
89
3
3
Order By: Relevance
“…It has been known that plasma aldosterone and renin activity may oscillate in normal women during the ovarian cycle usually increasing in the luteal phase, [21][22][23][24] but to our knowledge no report has addressed the potential relevance of this aspect in the first-step laboratory screening of primary aldosteronism in low-renin hypertensive women and no recommendation is made on this aspect in the practical guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that plasma aldosterone and renin activity may oscillate in normal women during the ovarian cycle usually increasing in the luteal phase, [21][22][23][24] but to our knowledge no report has addressed the potential relevance of this aspect in the first-step laboratory screening of primary aldosteronism in low-renin hypertensive women and no recommendation is made on this aspect in the practical guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone levels are known to vary considerably in the same subject and various factors have been identified that affect this variability; among them sodium and potassium balance, posture, circadian rhythm and drug treatment are well known. 19,20 Another determinant of aldosterone variability that has been identified in normal women is the ovarian cycle [21][22][23][24] but this has not so much been taken into account in hypertension.…”
Section: -13mentioning
confidence: 99%
“…A gender difference may be revealed, or perhaps, overestimated, when all women are studied during the follicular phase, at which time sympathetic activity tends to be relatively low. 22,41 Another potential limitation of our study is that some of the women were ingesting oral contraceptive pills. In a previous study, oral contraceptives influenced baroreflex heart rate and sympathetic vasomotor tone regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Greenberg et al 11 , Hirshoren et al 12 and Pai et al 13 also have demonstrated similar findings. Again, sato et al 1 observed similar results when compared SBP and DBP during follicular and luteal phases of menstrual cycle.…”
Section: Discussionmentioning
confidence: 60%